Synthesis and Structural Characterization of 4-Hydroxyanilinium 3,4,5,6-Tetrabromo-2-(methoxycarbonyl)benzoate Methanol Monosolvate - Zu Pei, Liang; Jian, Li; Xiao Ru, Pan (Asian Journal of Chemistry, 2015)
The compound, 4-hydroxyanilinium 3,4,5,6-tetrabromo-2-(methoxycarbonyl)benzoate methanol monosolvate (C16H15NO6Br4, Mr = 636.93) was synthesized and characterized by single crystal X-ray diffraction. The crystal belongs to triclinic, space group P-1, with a = 7.0403(9), b = 10.8695(12), c = 13.9844(16) Å, b = 82.852(2)°, V = 1033.4(2) Å3, Z = 2, Dc = 2.047 g/cm3. The final refinement gave R = 0.1051, wR(F2) = 0.2658 for 3,482 observed reflections with I > 2s(I). The asymmetric unit of the title compound contains one 4-hydroxyanilinium cation, one 3,4,5,6-tetrabromo-2-(methoxycarbonyl)benzoate anion and one methanol molecule. In the anion, the mean planes of the methoxycarbonyl and carboxylate groups form dihedral angles of 66.8 (3) and 88.8 (3)°, respectively with the benzene ring. In the crystal, intermolecular N---H...O and O---H...O hydrogen bonds connect the components of the structure to form a network.